Zoroastrianism - Moore, George Foot (Harvard theological review, 1912)
The religion whose adherents call themselves “Worshippers of Mazda,” the Wise God, and which we commonly name after its founder Zoroastrianism, is in many ways of peculiar interest. It is the only monotheistic religion of Indo-European origin, as Judaism is the one independent Semitic monotheism. Zoroastrianism is, further, eminently an ethical religion, both in its idea of God and of what God requires of men. It presents itself as a revelation of God's will through his prophet. His will is that men, renouncing the false gods, should serve the Wise Lord alone, obey his word, and contend on his side for the defeat of evil and the triumph of all good in nature and society and in the character of the individual. The prophet warns men that the day of the Lord is at hand, an ordeal by fire in which God will separate between those who serve him and those who serve him not, and of the endless blessedness or the unfathomable misery beyond. God has his allies not only among men but among the hosts of spirits; to the hierarchy of good powers corresponds a hierarchy of evil. In the endeavor to clear God of the responsibility for evil, Zoroastrianism recognized a powerful head of the evil spirits, a devil. But it had firm faith in the final triumph of good and the end of all evil. When that day shall come, all the dead will be raised to stand at the bar of God in the grand assize and receive the just recompense of reward. The main features of this eschatology were adopted by the Jews and adapted to the premises of their own religion; through Judaism it passed to Christianity, where it was fused with elements of diverse origin; from Judaism and Christianity, and to some extent directly from later Zoroastrianism, Mohammedanism inherited it. The orthodox beliefs about the hereafter of the world and the individual entertained by the nations of Western Asia, Europe, and America, are thus ultimately derived in no small part from Zoroastrianism; only in the farther East, in India, China, and Japan, does another system prevail.